SISTEM INFORMASI PENJUALAN ALAT MUSIK BERBASIS WEB PADA TOKO ALAT MUSIK TESSELLANT INSTRUMENT WORKS JAKARTA - Zulfikar Rizqi; Marhaeni Marhaeni (JURNAL REKAYASA INFORMASI, 2021)
The spread of information technology around the world has many changes in systems and lives. Internet technology turns conventional systems into digital systems, where everything becomes efficient and effective. In terms of the utilization of information technology in the Tessellant Instrument Works Music Store, the processing of transaction data is still conventional or uncomputed, therefore data processing is less effective and efficient. The new system proposes an integrated system of online trading and user- friendly. In designing this system, the researchers used six stages in the Spiral method, namely information gathering, planning, analysis, designing, application creation and program testing. The sales application is created using PHP and use MySQL database. The researchers conducted testing as part of the development. Keywords : Music Store, Spiral Method, Sales System